Upaya Meningkatkan Ketertarikan Peserta Didik Pada Pembelajaran Matematika Materi Perkalian Melalui Media Permainan Ular Tangga Di Kelas I SDN Pedagangan III Kecamatan Tiris Probolinggo Tahun Ajaran 2023/2024 - Diana Lufi; Fauzi Fadliansyah (Desanta Publisher, 2024)
This research aims to determine the use of snakes and ladders media which has an effect on improving Mathematics learning outcomes using the snakes and ladders game media. This type of research is Classroom Action Research (PTK). This research was carried out in 2 cycles, the design of this research used the Kurt Lewin model which has 4 aspects, namely: 1. Planning 2. Action 3. Observation 4. Reflection. Classroom Action Research (PTK) was carried out at SDN Pedagangan III which is in Pedagangan Village, Tiris District, Probolinggo Regency, East Java Province. Class I students numbered 15 people, of which 9 were men and 6 were women. In this research, the results have been obtained that before using game media, the motivation and learning outcomes of class I students can be said to be low, from 58.6% in the pre-cycle, there was an increase to 72.6% in the first cycle and experienced an increase and good Mathematics learning outcomes were achieved. increased to 84.6%. Thus, the results obtained have achieved success, the teacher hopes to be able to apply the snakes and ladders method in learning Mathematics, Multiplication Material so that it can attract students' interest in learning and can develop it into a more interesting game and create games that make students more active in participating in Mathematics learning.